The Implementation of British Parliamentary Debate Style Training to Improve Second Semester Student’s Speaking Ability at English Education Study Program of Baturaja University - Henny Yulia; Nanda Aprilita (Universitas Jambi, Magister Program of English Education Department, 2017)
The problem of this study was concerned with British Parliamentary Debate Style Training to improve second semester students’ speaking ability at English Education Study Program at Baturaja University. The objective of this study was to find out whether it was significantly effective or not to implement British Parliamentary Debate Style Training to improve second semester students’ speaking ability at English Education Study Program at Baturaja University. This study used pre experimental design covered pre test before the treatment and post test after the treatment. The second semester students of English Education Study Program at Baturaja University were the population. The number of the population was 18 students. The researcher took class A as a sample by using cluster random sampling. Based on the calculation, the sample of the study was 12 students and the significance level (α = 0.05). The result of paired t test has value of ttest (5.033) was more than the value of ttabel (2.2009) with df = 12-1 = 11. The value of Sig. (2-tailed) was 0.000 lower than the value of significance level (α = 0.05). This result showed that the alternative Hypostudy (Ha) was accepted. It meant that British Parliamentary Debate Style Training could improve second semester students’ speaking ability of English Education Study Program. Keywords: Speaking, Implementation, Debate, Baturaja University.